The regenerative mechanisms of platelet-rich plasma: A review. (August 2021) - dos Santos, Rafael Gonzalez; Santos, Gabriel Silva; Alkass, Natasha; Chiesa, Tania Liana; Azzini, Gabriel Ohana; da Fonseca, Lucas Furtado; dos Santos, Antonio Fernando; Rodrigues, Bruno Lima; Mosaner, Tomas; Lana, José Fábio
Abstract: Orthobiologics continue to gain popularity in many areas of medical science, especially in the field of regenerative medicine. Platelet-rich plasma derivatives are orthobiologic tools of particular interest. These biologic products can be obtained via centrifugation of a patient's whole blood and the components can then be subsequently isolated, concentrated and ultimately administered into injured tissues, particularly in areas where standard healing is disrupted. The elevated concentration of platelets above the basal value enables accelerated growth of various tissues with minimal side effects. The application of autologous orthobiologics is a relatively new biotechnology undergoing expansion which continues to reveal optimistic results in the stimulation and enhanced healing of various sorts of tissue injuries. The local release of growth factors and cytokines contained in platelet alpha granules accelerates and ameliorates tissue repair processes, mimicking and supporting standard wound healing. This effect is greatly enhanced upon combination with the fibrinolytic system, which are essential for complete regeneration. Fibrinolytic reactions can dictate proper cellular recruitment of certain cell populations such as mesenchymal stem cells and other immunomodulatory agents. Additionally, these reactions also control proteolytic activity in areas of wound healing and regenerative processes of mesodermal tissues including bone, cartilage, and muscle, which makes it particularly valuable for musculoskeletal health, for instance. Although many investigations have demonstrated significant results with platelet-rich plasma derivatives, further studies are still warranted.